Pre-exposure prophylaxis with hydroxychloroquine for COVID-19: a double-blind, placebo-controlled randomized clinical trial - Berta Grau-Pujol (BMC, 2021)
Abstract Background Pre-exposure prophylaxis (PrEP) is a promising strategy to break COVID-19 transmission. Although hydroxychloroquine was evaluated for treatment and post-exposure prophylaxis, it is not evaluated for COVID-19 PrEP yet. The aim of this study was to evaluate the efficacy and safety of PrEP with hydroxychloroquine against placebo in healthcare workers at high risk of SARS-CoV-2 infection during an epidemic period. Methods We conducted a double-blind placebo-controlled randomized clinical trial in three hospitals in Barcelona, Spain. From 350 adult healthcare workers screened, we included 269 participants with no active or past SARS-CoV-2 infection (determined by a negative nasopharyngeal SARS-CoV-2 PCR and a negative serology against SARS-CoV-2). Participants allocated in the intervention arm (PrEP) received 400 mg of hydroxychloroquine daily for the first four consecutive days and subsequently, 400 mg weekly during the study period. Participants in the control group followed the same treatment schedule with placebo tablets. Results 52.8% (142/269) of participants were in the hydroxychloroquine arm and 47.2% (127/269) in the placebo arm. Given the national epidemic incidence decay, only one participant in each group was diagnosed with COVID-19. The trial was stopped due to futility and our study design was deemed underpowered to evaluate any benefit regarding PrEP efficacy. Both groups showed a similar proportion of participants experiencing at least one adverse event (AE) (p=0.548). No serious AEs were reported. Almost all AEs (96.4%, 106/110) were mild. Only mild gastrointestinal symptoms were significantly higher in the hydroxychloroquine arm compared to the placebo arm (27.4% (39/142) vs 15.7% (20/127), p=0.041). Conclusions Although the efficacy of PrEP with hydroxychloroquine for preventing COVID-19 could not be evaluated, our study showed that PrEP with hydroxychloroquine at low doses is safe. Trial registration ClinicalTrials.gov NCT04331834 . Registered on April 2, 2020.